On the universality of weak interactions - Itô, D.; Ragusa, S.; Zimerman, A. H. (Springer Nature, 1962)
In classical physics the electromagnetic interactions can be introduced, on account of their universality, by the well-known formal procedure: p μ→p μ-(e/c)A μ. The universal gravitational interaction is also introduced formally as a change in metric: δμν→g μν=δμν+χμν. In analogy with these classical examples of universal interactions we shall propose here to introduce the universal leptonic interactions by a similar formal procedure of replacing baryonic currents J μ, Y μ (strangeness-conserving and violating currents) and boson-field operators ∂ μπ and ∂ μ K appearing in the non-leptonic interaction Lagrangian: ℒ=l[J μ + ∂ μ K+Y μ + ∂ μπ+h. c.] by J μ→J μ+αL μ, Y μ→Y μ+βL μ, and ∂ μπ→∂ μπ+αr 0 L μ, ∂ μ K→∂ μ K+βr 0 L μ, where {Mathematical expression} is the usual leptonic current, r 0=1.4·10-13 cm; α and β are constants which can be determined as α=1/4 and β=1. Then almost all leptonic interactions are introduced by this formal procedure and the predictions from the new Lagrangian are compared with experiments. The agreements are satisfactory, e.g., the well-known small probabilities of the leptonic decays of hyperons are reproduced by our new Lagrangian. © 1962 Società Italiana di Fisica.